Characteristics of Energy Evolution and Failure Mechanisms in Sandstone Subject to Triaxial Cyclic Loading and Unloading Conditions - Jinrui Zhang; Yi Luo; Hangli Gong; Xianqi Zhang; Shankun Zhao (Applied Sciences)
This study investigates the energy dynamics of sandstone subjected to failure in conditions typical of deep underground construction. Research was conducted using both standard triaxial compression and cyclic loading–unloading techniques at six distinct confining pressures, with the objective of elucidating the deformation and failure processes of rock materials. The tests demonstrated that, regardless of the stress path, sandstone primarily fails through shear under different confining pressures, which also reduces the formation of secondary cracks. The energy transformation observed during cyclic loading and unloading processes exhibits a distinctive peak-like distribution, marked by an inflection point that indicates changes in energy distribution. In the initial stages of the loading cycle, the energy profile of the rock increases, characterized by a condition in which the energy stored elastically exceeds the energy dissipated. Nevertheless, subsequent to reaching peak stress, there is a rapid transmutation of elastic strain energy into other forms, culminating in a pronounced elevation in the ratio of dissipated energy, which ultimately achieves a state of equilibrium influenced by the confining pressures. The study introduces the energy consumption ratio (Ke) as a metric for assessing rock damage accumulation and stability, noting a critical pattern where Ke decreases and then spikes at the rock’s failure point, with K = 1 identified as the critical threshold for failure. This comprehensive analysis illuminates the intricate relationship between energy distribution patterns and the stability of rock structures, thereby enhancing our understanding of failure mechanisms from an energetic perspective.